A Critical Analysis of Review of Literature on Domestic Violence against Working Women - Pushpa Hongal; Dr. Uttamkuamr Kinange; Dr. Gururaj Phatak (International Journal of Engineering and Management Research, 2021)
In our society violence is prevalent everywhere, be it outside or inside the four walls of the home. Domestic Violence includes physical abuse, emotional, economic, verbal, and sexual abuse. The social stigma of public dishonor is the greatest cause for a woman to become trapped in this frightful environment. General observation reveals that a woman who is dependent financially on her partner or her family is more prone for violence, but it is not always true. Working women, who is equally contributing for her family as other counterpart, is also equally prone for domestic violence either from her spouse or family members. Several studies have shown that working women in India is also caught up under the vicious circle of domestic violence .Many scholarly articles are available on these issues. Here in this paper an attempt is made by researchers to review different scholarly articles and understand why domestic violence against working women happens though she is financially empowered, also to examine its different forms and the factors which are making her endure. This article is based on critical analysis of literature review and secondary data.